Nutrition for Health and Fitness: Sodium in Your Diet - Linda B. Bobroff (EDIS)
Revised! FCS8219, a 6-page illustrated fact sheet by Linda B. Bobroff, provides facts about sodium, high blood pressure, and how to read food labels and cook with less sodium. Includes references, sodium intake checklist, and recipes for low sodium foods. Published by the UF Department of Family, Youth and Community Sciences, October 2010.